A BLOCKCHAIN-BASED MODEL FOR PROVISION OF INCENTIVES TO RARE BLOOD GROUP DONORS - BUNEI, CHEBET LEAH (Kabarak University, 2025)
A critical requirement in achieving universal healthcare in Kenya is to maintain a consistent and adequate blood supply in the blood bank. Rare blood group donors, specifically those with AB-negative, B-negative, A-negative, and O-negative blood types, played a vital role in providing life-saving support to patients with special medical needs. However, the scarcity of these blood types posed a significant challenge, especially during emergencies or periods of high demand. Donor motivation remained low due to ineffective incentive systems, as traditional blood donation management platforms often lacked transparency, poor donor identification, and delayed or inadequate reward mechanisms. To address these challenges, the researcher developed a blockchain-based model prototype designed to provide secure, transparent, and trustworthy incentives for rare blood group donors. The study focused on the design, development, and evaluation of a model that integrated Solidity smart contracts and was implemented using React.js, accessible at https://grandmullah.github.io/donor. The model featured a token reward module that automatically generated and distributed digital tokens to verified donors, allocating 250 tokens for AB−, 230 for O−, 200 for B−, and 150 for A−, which could be redeemed for benefits such as subsidized medical care, free checkups, preferential services, and T-shirts. To ensure data protection and regulatory compliance, the model employed encryption, access controls, and adherence to data privacy laws. The research adopted a systematic literature review to examine existing models and used the agile methodology in prototype development. Testing with dummy data was conducted at the Nakuru County Referral and Teaching Hospital blood donor unit. In conclusion, the blockchain-based model for provision of incentives to rare blood group donors demonstrated a viable and secure solution to the challenges in blood donation management, enhancing trust, transparency, and donor motivation, particularly among rare blood group donors.
Keywords: Blockchain, Model, Smart Contract, Confidentiality, Donors